STROKES - ASSOCIATION WITH PHYSICAL ACTIVITY AND COVID -19. REHABILITATION AFTER STROKE SUCH AS MUSICGLOVES THERAPY - Aleksandra Woskowska; Weronika Woskowska; Anna Hanslik; Magdalena Mendak; Agata Białek; Monika Klimczak; Magdalena Domisiewicz (International Journal of Innovative Technologies in Social Science, 2025)
This article is a systematic review of strokes, their classification, diagnosis and the influence of physical activity on the incidence, taking into account training intensity. In addition, this publication addresses the aspect of the relationship between strokes and COVID-19. Also included is information on an innovative method of upper limb rehabilitation in stroke patients - Music Glove. Aim of study and materials: In order to describe the impact of physical activity on the risk of stroke, taking into account all the above-mentioned aspects, a review of the PubMed, Google Scholar, ResearchGate, Elsevier and ViaMedica databases was conducted. Finally, 24 review articles, meta-analyses, case reports, clinical and comparative studies were included, and WHO guidelines and other scientific literature were used as support. Conclusion: Strokes are the second most common cause of death worldwide, as well as the most common cause of disability. One of the important, modifiable, and often overlooked risk factors for a stroke incident is a lack of or low physical activity. It is worth emphasizing that a positive effect is attributed to regular, moderate physical activity. High-performance, high-intensity sports can be dangerous in terms of the risk of stroke.